2020
DOI: 10.1038/s41598-020-61237-2
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Analysis of Demographic and Socioeconomic Disparities in Pediatric CNS Cancer Survival in the United States

Abstract: Previous studies have demonstrated effects of racial and socioeconomic factors on survival of adults with cancer. While less studied in the pediatric population, data exist demonstrating disparities of care and survival in pediatric oncology patients based on socioeconomic and racial/ethnic factors. Brain cancers recently overtook leukemia as the number one cause of childhood cancer fatalities, but demographic and socioeconomic disparities in these tumors have not been adequately studied. We obtained data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 16 publications
4
28
0
Order By: Relevance
“…In our study of 22,469 brain and CNS tumors diagnosed in children aged 0 to 19 years and captured in the NCDB (2004-2016), we found overall and histologyspecific differences in survival by race/ethnicity such that Black and Hispanic children had worse survival than White children. The findings for Black children experiencing a higher risk of death align with previous publications 4 and with a recent report by Siegel et al 3 using National Cancer Registry data, who observed a 24% excess in death among Black patients, which was similar to our estimate of a 22% excess. However, they did not observe an excess risk of death among Hispanic patients in their study as we did herein.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study of 22,469 brain and CNS tumors diagnosed in children aged 0 to 19 years and captured in the NCDB (2004-2016), we found overall and histologyspecific differences in survival by race/ethnicity such that Black and Hispanic children had worse survival than White children. The findings for Black children experiencing a higher risk of death align with previous publications 4 and with a recent report by Siegel et al 3 using National Cancer Registry data, who observed a 24% excess in death among Black patients, which was similar to our estimate of a 22% excess. However, they did not observe an excess risk of death among Hispanic patients in their study as we did herein.…”
Section: Discussionsupporting
confidence: 92%
“…Brain tumors are the most common solid tumors in children 1 . Minority children are less frequently diagnosed with these tumors as White children have an incidence rate of 5 cases per 100,000 and Black and Hispanic children have a rate of 4 cases per 100,000 2 ; however, Black and Hispanic children experience an increased risk of death in comparison with White children 3,4 even after accounting for age, socioeconomic status, stage of disease, and treatment as adjustment factors in the analysis 5 . Often times, racial/ethnic survival disparities are explained by or linked to existing differences in socioeconomic status 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite similar reported survival rates for Hispanics, African Americans, Asians and White children, gaps in understanding disparities in cancer still exist [26,27]. Racial and ethnic disparities in childhood CNS tumor survival appear to have their roots at least partially in post-diagnosis factors, potentially due to the lack of access to high quality care, leading to poorer overall outcomes [28,29]. These disparities include differences or delays in treatment.…”
Section: Susceptibility To Zoonoses By Racementioning
confidence: 99%
“…Additional disparities include impaired access to care and clinical trials, differences in cancer biology, treatment non-adherence, language barriers, and implicit racial bias. Although socioeconomic factors may account for a large proportion of disparities seen, the causes of disparities are complex and interconnected and still need to be better understood [27,28]. Further studies on how systemic racism and oppression impact pediatric cancer are needed.…”
Section: Susceptibility To Zoonoses By Racementioning
confidence: 99%
“…Despite the improvement in the prognosis of brain tumors achieved by incorporating advanced surgical technologies and knowledge in molecular classification (2), the factors associated with differential survival are still unclear. An important set of factors and a persistent public health concern are inequalities by sociodemographic characteristics in access to general health care, neurosurgical, and neuro-oncological (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%